1993
DOI: 10.1073/pnas.90.16.7656
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide, an endogenous cannabimimetic eicosanoid, binds to the cloned human cannabinoid receptor and stimulates receptor-mediated signal transduction.

Abstract: Arachidonylethanolamide (anandamide), a candidate endogenous cannabinoid ligand, has recently been isolated from porcine brain and displayed cannabinoid-like binding activity to synaptosomal membrane preparations and mimicked cannabinoid-induced inhibition of the twitch response in isolated murine vas deferens. In this study, anandamide and several congeners were evaluated as cannabinoid agonists by examining their ability to bind to the cloned cannabinoid receptor, inhibit forskolin-stimulated cAMP accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
281
0
18

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(315 citation statements)
references
References 23 publications
16
281
0
18
Order By: Relevance
“…catalepsy, hypothermia and analgesia) (3, and, for review, 19). Anandamide was also shown to activate transfected cannabinoid receptors in Chinese hamster ovary cells, thereby triggering cannabinoidassociated transmembrane signalling events, thus further substantiating its role as an endogenous cannabinoid receptor ligand (4,5, and, for review, 6).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…catalepsy, hypothermia and analgesia) (3, and, for review, 19). Anandamide was also shown to activate transfected cannabinoid receptors in Chinese hamster ovary cells, thereby triggering cannabinoidassociated transmembrane signalling events, thus further substantiating its role as an endogenous cannabinoid receptor ligand (4,5, and, for review, 6).…”
Section: Introductionmentioning
confidence: 82%
“…The possibility that, in addition to anandamide, other NAEs, with either saturated or polyunsaturated acyl moieties, are produced by mammalian neurons and participate in neuronal signalling has been strongly suggested by recent investigations. In these studies, several additional NAEs have been shown, on one hand, to exert cannabinoid-like activities similar to those of anandamide (5,15) and, on the other, to be produced by intact neurons challenged with various physiological stimuli (16) and to be present in brain tissue (15). Therefore, it can be foreseen that an ever increasing number of efforts will be aimed, in the next years, at fully understanding the physiological role of this important class of lipids, as well as the molecular mechanisms by which their synthesis and inactivation are regulated.…”
Section: Introductionmentioning
confidence: 96%
“…Anandamide induces AA release from J774 mouse macrophages, and this is blocked by pertussis toxin, an inhibitor of G i/o proteins . However, anandamide also induces AA release in cells that do not express CB 1 or CB 2 receptors (Felder et al, 1993;Felder et al, 1995). THC induces AA release from RAW 264.7 mouse macrophages, and this is likely mediated by the CB 2 receptor (Hunter & Burstein, 1997).…”
Section: Aa Releasementioning
confidence: 99%
“…NAE displayed similar in vivo and in vitro effects as a cannabinoid receptor agonist acting through the CB1 cannabinoid receptor (for review, see Felder and Glass, 1998). NAE induces antinociception, hypomotility, hypothermia, and catalepsy when injected into mice, and, in vitro, it is capable of inhibiting forskolininduced accumulation of intracellular cyclic AMP and Ntype Ca2+ channels in several types of cells (Felder et al, 1993;Vogel et al, 1993).…”
Section: N-arachidonoylethanolamidementioning
confidence: 99%